A tellurium short-wave infrared photodetector with fast response and high specific detectivity. Issue 36 (1st September 2022) - Yan, Yafei; Xia, Kai; Gan, Wei; Yang, Kemeng; Li, Gang; Tang, Xi; Li, Liang; Zhang, Changjin; Fei, Guang Tao; Li, Hui
Abstract : Elementary tellurium based short-wave infrared photodetector with fast response. Abstract : Two-dimensional (2D) elementary tellurium (Te) has attracted intensive attention due to its potential applications in short-wave infrared photodetector devices. Here, we report hydrothermally synthesized 2D Te nanoflakes for short-wave infrared photodetectors with high performance. A Te-based photodetector exhibits a peak responsivity of 51.85 A W −1 at a 1550 nm wavelength, attributed to the efficient absorption of the phonons of 2D Te nanoflakes. Besides, the rising and decay time of the Te photodetector is calculated to be ∼19 μs and ∼21 μs, respectively, due to the rapid diffusion of charge carriers. In addition, Te-photodetectors exhibit a high specific detectivity ( D *) of 1.88 × 10 10 Jones and a superior external quantum efficiency (EQE) of 4148%. Our findings have demonstrated the development of high-performance short-wave infrared photodetectors with fast responses based on 2D Te nanoflakes.